Influence of a genetic difference confined to mutation of H-2K on the incidence of pregnancy block in mice. - Yamazaki, K (1986)
In mice, pregnancy is often terminated when the stud male is removed and the pregnant female is exposed to the presence or scent of an unfamiliar male. It is reported here that the incidence of such blocking of pregnancy was higher when the stud and unfamiliar male differed by mutation of the H-2K class I gene of the major histocompatibility complex than when the stud and unfamiliar males were genetically identical. Thus, the olfactory distinction of mice differing by mutation of the H-2K gene, previously demonstrated after training of mice in a Y maze, can spontaneously influence neuroendocrine communications affecting reproduction.